2010
DOI: 10.2478/s11756-010-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

The predatory mite Typhlodromus pyri (Acari: Phytoseiidae) as a biocontrol agent of Eriophyes pyri (Acari: Eriophyidae) on pear

Abstract: The intensity of symptoms on infested leaves was also different depending on treatments and years. The average biological activity was 82.4% in plots receiving releases of T. pyri and 58.8% in plots treated with Polysulphide-Ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The research showed that this biocontrol agent is efficient in controlling leaf blister mites in orchards. Moreover, T. pyri is able to survive and reproduce on the alternative food sources like fungi, pollen or plant juices, so the treatment with this mite is not necessary to be so often repeated [13].…”
Section: Harmfulness and Methods Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The research showed that this biocontrol agent is efficient in controlling leaf blister mites in orchards. Moreover, T. pyri is able to survive and reproduce on the alternative food sources like fungi, pollen or plant juices, so the treatment with this mite is not necessary to be so often repeated [13].…”
Section: Harmfulness and Methods Of Controlmentioning
confidence: 99%
“…Chemical control is possible to be carried out only in a period before forming the blisters, otherwise it will be not efficient [13]. It was showed that satisfying effects can bring pesticides containing sulphur.…”
Section: Harmfulness and Methods Of Controlmentioning
confidence: 99%
“…The predatory mite Typhlodromus pyri Scheuten, 1857 represents one of the most important biocontrol agents of phytophagous mites occurring in orchards and vineyards in many countries of Europe and North America (Helle & Sabelis 1985;Zacharda 1989;Mc-Murtry 1992;Schausberger 1999;Sengonca et al 2003;Duso 1989;Duso et al 2003;Sekrecka & Niemczyk 2006;Praslička et al 2011). Van de Vrie (1964) found that the populations of T. pyri in their growing season are wide-spread during the whole summer.…”
Section: Introductionmentioning
confidence: 99%